Exploring Students’ Speaking Anxiety in New Normal Era : Descriptive Study - Wulandari, Triyani; Wardhani, Ika Desy; Sabartono, Ribut (Linguapedia, 2023)
This research aims to find out how high the level of anxiety is among students, especially English Language Learners, they really experience difficulties in speaking which causes self-confidence and anxiety problems. Storytelling can improve speaking skills but poses difficulties due to previously exclusive online learning. Storytelling significantly benefits English learning in the new normal era, boosting  confidence  and  outcomes.  While  students  generally  express  interest, some  remain  hesitant.  Inconsistent  media  use  by teachers  needs  rectification. Anxiety persists, especially in remote learning due to physical restrictions and limited social interaction. Teachers must creatively engage students, utilize technology, and foster a supportive environment to address these issues and optimize storytelling's benefits.